Villard de Honnecourt, architecte du XIIIe siècle - Wirth, Jean (Titre courant, 2015)
The only document we have by a 13th-century architect, the Album of Villard de Honnecourt has been the subject of writings by art and architectural historians since the 19th century and has been considered the work of an amateur since the 1970s. Jean Wirth sheds new light on the question, based on a philological study of the manuscript, and proves that Villard himself is the author of the technical drawings relating to construction. He goes on to provide convincing analyses of the art of drawing and its numerous applications, from drawing from nature to architectural plans. Drawings relating to engineering, geometry and stereotomy are treated individually, in order to convey as clearly as possible the technical processes they illustrate. An examination of the architect's travels, the monuments he saw and his stylistic evolution allows for an accurate, corrected chronology of this work, previously considered outdated. This intelligent and detailed study will be a landmark in the rehabilitation of Villard de Honnecourt's reputation.